Costos por procesos de producción del chocolate artesanal, en la asociación de campesinos Lamanenses “Ascala”, cantón La Maná, provincia de Cotopaxi, año 2022. - Ordóñez Amores, Lourdes Susana (2023)
The present project was oriented to solve the following problem: How did the process costing system help determine the unit cost of the product in the Asociación de Campesinos Lamanenses "ASCALA" located in the canton La Maná, province Cotopaxi? And the general objective was to develop a production process costing system in the Asociación de Campesinos Lamanenses "ASCALA" for the determination of unit costs. From a qualitative and quantitative approach, interview and survey techniques were used, where a diagnosis was made that allowed the achievement of the objective and the following conclusions: A flow chart of processes and activities was developed for the elaboration of natural artisan chocolate by this Association, which consists of three steps (purchase of inputs, preparation of raw material, and final product for sale); it was identified that the costs incurred in this activity are lower than the sale price of the product, which makes the process profitable. It was determined that ASCALA does not have a production cost model and a process cost model was designed for the production of natural artisan chocolate, which helps to minimize expenses, and time and to have complete information that allows identifying the real cost of the product. This research project was important because, through the development of a process costing system, the microenterprise learned the real cost incurred in the production of natural artisan chocolate, identifying the value of each production process involving raw materials, labor, and indirect manufacturing costs.